Teachers’ Challenges in Vocabulary Instruction for Students Showing Slow Learning Characteristics: A Case Study - Murni Amalia; Didik Santoso (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
Vocabulary instruction is essential in English language learning, yet it becomes more challenging when teachers work with students showing slow learning characteristics. These students often require more time, repetition, and structured support to understand, retain, and use new words. This study aimed to examine the challenges faced by an English teacher in implementing vocabulary instruction for such students in a junior secondary classroom. Using a qualitative case study design, data were collected through semi-structured interviews, non-participant classroom observations, and field notes involving an English teacher and a homeroom teacher at a private junior high school in Batu Bara Regency, North Sumatra. The data were analyzed using thematic analysis. The findings revealed eight major challenges: maintaining students’ focus, supporting vocabulary retention, addressing limited vocabulary knowledge, adjusting lesson pace, managing a large class, sustaining engagement, dealing with limited instructional time, and responding to home-related factors. The study concludes that vocabulary instruction for slow learners requires adaptive, structured, and inclusive teaching. This study contributes practical insights for developing more responsive vocabulary instruction in Indonesian junior secondary EFL classrooms.